Relationship of Religiosity and Personality Dimensions with Rehabilitation Pracririoner Students Satisfaction with their Clinical Experiences - Yaser Rezapour-Mirsaleh; Kianoush A'bdi; Masoud Karimlou; Shahnaz Reyhani-Kivi (University of Social Welfare and Rehabilitation Sciences, 2010)
Obgective: The purpose of present study was to investigate the relationship of religiosity and personality dimensions with satisfaction of rehabilitation practitioner students about their clinical experiences as a therapist. Materials & Methods: In this descriptive study, three hundreds eighteen rehabilitation practitioner students including onehundred forty physical therapy students, ninty seven occupational therapy students, and eighty one speech therapy students were selected by randomized and stratified sampling method. Data were collected through Islamic religiosity scale, NEO inventory and job satisfaction questionnaire, and analyzed by statistical methods such as: Pearson correlation coefficient and multiple regression analysis. Results: The finding showed that satisfaction from clinical experiences was positively and significantly correlated with religiosity, religious pretentiousness, and three dimensions of personality include extraversion, agreeable and consciousness, and was negatively and significantly correlated with neuroticism and religious disorganization in all of rehabilitation students. (P<0.0001). Results of multiple regression analysis showed that in physical therapy, religiosity and extraversion and agreeable, in occupational therapy students, extraversion ,consciousness and gratification and in speech therapy students, religiosity and religious disorganization have more power to predict of satisfaction with clinical experiences. Conclusion: With regarding to results, can concluded that religiosity is important factor to predict of satisfaction from clinical experiences in physical therapy, occupational therapy and speech therapy practitioner students.